KEPUASAN WISATAWAN TENTANG DAYA TARIK WISATA PANTAI AIR MANIS PADANG - Rindani, Liantika; Silfeni, Silfeni; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This research purpose to know howsatisfiedthetourists of Pantai Air Manis Padang tourism which include four of tourist’s attraction indicators that are attraction, accessibilities, amenities and ancillary services. This research consists of four indicators are: attraction, accessibilities, amenities, and ancillary services. This type of research is descriptive research using survey method. Population in this research amounted to 2.023 people’s. Sampling technique is non probability sampling, using incidental sampling. Sample number in this research amounted for 96 people’s. Data collection using a questionnaire that tested for validity and reliability. Based on the Result of the research shown that tourist satisfaction about tourist attraction of Pantai Air Manis Padang tourism is fairly satisfy categorized with average value 143,78 at the range score 140 - <170 with 50% percentage. Kata kunci: kepuasan wisatawan, daya tarik wisata, Pantai Air Manis Padang1Prodi D4